Community Livelihood Assets in Ketapanrame Tourism Village - Ardhana, Hashfian; Prayitno, Gunawan; Hidayat, AR. Rohman Taufiq; Sugo, Ken (Journal of Regional and Rural Studies, 2025)
This study analyzes the condition of five livelihood assets in Ketapanrame Tourism Village to evaluate the implications of tourism development for household livelihoods. Primary data were collected through a household survey using simple random sampling, involving 350 respondents. Data analysis employed descriptive statistics based on a five point Likert scale to capture variations in asset ownership and access. The findings show that physical and social assets are relatively well developed. Most households have adequate access to housing, electricity, clean water, and basic public facilities, supported by a relatively high level of trust in village institutions and the village owned enterprise. In contrast, human and financial assets remain weak. Participation in training programs is limited, skills relevant to income diversification are unevenly distributed, and access to health insurance and financial savings is not evenly shared among households. A considerable proportion of respondents report household incomes at or below the regional minimum wage, indicating limited economic gains from tourism activities. Natural assets contribute selectively to livelihoods. Environmental cleanliness has improved, yet the productive use of village land differs across hamlets, with several areas remaining underutilized. These results indicate that tourism development has not uniformly strengthened all livelihood assets. The study highlights the need for targeted interventions, particularly in enhancing human capital and financial capacity, to ensure that tourism contributes more effectively to livelihood improvement. Strengthening skills development, expanding social protection, and promoting productive use of local natural resources are essential to support more inclusive and resilient livelihood outcomes in Ketapanrame Tourism Village.